Histological and biochemical changes offering resistance to Eumusae leaf spot disease in banana - Milsha George; Anita Cherian K.; Deepu Mathew (Academia Biology)
Eumusae leaf spot disease, caused by the fungus Pseudocercospora eumusae, is a serious foliar disease affecting banana plants leading to up to 90% yield losses. Five Eumusae leaf spot resistant accessions, ‘Pisang Lilin’, ‘BRS 1’, ‘BRS 2’, ‘FHIA 01’, and ‘FHIA 23’, and five susceptible accessions, ‘Nenthran’, ‘Grand Naine’, ‘Robusta’, ‘Moris’, and ‘Kadali’, were used to compare histological and biochemical changes under healthy and infected conditions. The resistant accessions showed thicker cuticle, epidermis, and mesophyll tissues compared to the susceptible ones in both infected and healthy leaves. The stomatal density (the number of stomata per mm2) and stomatal pore width were greater in the susceptible accessions. The levels of phenolic compounds were higher in the healthy leaves of the resistant accessions compared to those of the susceptible ones, for which the levels decreased upon infection. Similarly, higher activity of the defence-related enzymes peroxidases, polyphenol oxidases, and phenylalanine ammonia lyases was found in the infected samples of the resistant accessions. Screening the lines with the Sequence Characterized Amplified Region (SCAR) marker linked with resistance to Sigatoka leaf spot disease has generated amplicons in the resistant accessions alone, confirming that this marker can be used successfully in marker-assisted breeding for resistance in banana plants. Cytological adaptations, elevated levels of biochemical components, and defence genes in the resistant accessions contribute to P. eumusae defence in banana plants.